Sources of Agricultural Information - Manjunatha, K. K. (Journal of Information and Knowledge, 1991)
Identifies the basic concepts in literature published in Agriculture Sciences. Varieties of information sources, variations in the subjects, conventional, primary, secondary, and tertiary literature are identified and described. Computer-based bibliographic services are analyzed.